Association of serum levels of p, p'- Dichlorodiphenyldichloroethylene (DDE) with type 2 diabetes in African American and Caucasian adult men from agricultural (Delta) and non-agricultural (non-Delta) regions of Mississippi. Issue 6 (19th March 2019) - Meek, Edward C.; Jones, Dana Dale; Crow, J. Allen; Wills, Robert W.; Cooke, William H.; Chambers, Janice E.
ABSTRACT: Epidemiological associations were reported in several studies between persistent organochlorine organic pollutants and type 2 diabetes mellitus (T2D). Mississippi is a highly agricultural state in the USA, particularly the Delta region, with previous high usage of organochlorine (OC) insecticides such as p, p' - dichlorodiphenyltrichloroethane (DDT). In addition, there is a high proportion of African Americans who display elevated prevalence of T2D. Therefore, this State provides an important dataset for further investigating any relationship between OC compounds and metabolic diseases. The aim of this study was to assess whether soil and serum levels of OC compounds, such as p, p' - dichlorodiphenyldichloroethylene (DDE), arising from the heavy historical use of legacy OC insecticides, might serve as an environmental public health indicator for T2D occurrence. Soil samples from 60 Delta and 60 non-Delta sites randomly selected were analyzed for the presence of OC compounds. A retrospective cohort study of adult men (150 from each region) was recruited to provide a blood sample for OC compound quantitation and select demographic and clinical information including T2D. Using multivariable logistic regression, an association was found between increasing serum DDE levels and T2D occurrence in non-Delta participants (those subjects with lower serum DDE levels), as opposed to Delta participants (individuals with higher serum DDE levels). Thus, while there was a relationship between serum DDE levels and T2D in those with lower burdens of DDE, the lack of association in those with higher levels of DDE indicates a complex non-monotonic correlation between serum DDE levels and T2D occurrence complicating the goal of finding a public health marker for T2D. Abbreviations: BMI, body mass index; CVD, cardiovascular disease; CDC, Center for Disease Control, United States of America; DDE, p, p' - dichlorodiphenyldichloroethylene; DDT, p, p' - dichlorodiphenyltrichloroethane; GC/MS, gas chromatography/mass spectrometry; GIS, geographic information system; GPS, global positioning system; HDL, high-density lipoprotein; HTN, hypertension; IDW, inverse distance weighting; IRB, Institutional Review Board; LDL, low-density lipoprotein; LOQ, limit of quantitation; NHANES, National Health and Nutrition Examination Surveys; POPs, persistent organic pollutants; OC, organochlorine; PCB, polychlorinated biphenyl; SIM, single-ion monitoring; T2D, type 2 diabetes mellitus; USA, United States of America.